Trocas simbólicas entre gerações: avós, netos e a literatura infantil - Silva, Camila Cuencas Funari Mendes e (2014)
This work aims at understanding the intergenerational relationships between grandparents and grandchildren in contemporary society. To this end, we analyze two works of Children's Literature as a form of manifestation of the importance of symbolic exchanges between generations. Selected Menina Nina: duas razões para não chorar, Ziraldo (2002) and A menina, o cofrinho e a vovó by Cora Coralina (2009). We adopt a psychoanalytic reading as a reference for analysis, since it excels in psychic construction of the individual, his unconscious design and its interaction with the socio-cultural environment , which allows to explore and reflect on the links between generations , thus serving as a research method and interpretation of relationships within the family . We confirm our hypothesis with writers - grandparents, here represented by Ziraldo and Cora Coralina, which produced works that highlight the experience with their grandchildren. Thus, grandparents, grandchildren and readers are active in recovery and symbolic transmission characters.